Elder poverty in an ageing world: Conditions of social vulnerability and low income for women in rich and middle-income nations - Timothy M. Smeeding; Qin Gao; Peter Saunders; Coady Wing (Luxembourg Income Study (LIS), 2008)
Social vulnerability for older persons, especially older women, due to insufficient income in retirement and earlier in life and low market earnings may be attributable to many sources, both demographic and economic, in our globalizing world. This paper examines the problems of population ageing, low incomes, and social spending on the elderly in comparative perspective, with a focus on older women in several rich and middle-income nations. We examine the United States, Canada, and a set of European nations using the LIS (Luxembourg Income Study) database, and three middle-income nations, focusing on Taiwan, China, and Mexico, around the turn of the century. In particular, we address what happens to older women as they outlive their husbands and have fewer claims on pensions and retirement wealth and maintain fewer productive capacities in the paid labor force. Issues that arise include the implications of policies relating to taxation, social spending, and transfers, as well as - of course - gender differentials in labor force participation, lifetime savings, and pre- and post-retirement incomes. Many older women, especially those in middle-income countries, also often share living arrangements with their adult children. We assess the net effects of existing policies on poverty and low income and wealth. While best practices may be identified, each nation must create its own set of mutually supportive policies that provide protection against global economic forces while at the same time encouraging self-reliance and efficient behavior, especially in the savings market. We conclude that policy can make a difference in outcomes, as shown for instance by the low cost but highly target effective Canadian efforts in fighting elder poverty, and by the Australian superannuation retirement income system. However, the developing economies of Mexico, China, and even Taiwan evolve from a tradition that does not yet support Western-style social insurance programs. In these nations, intergenerational co-residence is liable to be the key feature of antipoverty policy for elders in the coming decades.
Keywords: 330; Alte Menschen; Frauen; Armut; Soziale Ungleichheit; Soziale Lage; OECD-Staaten; Schwellenländer